1998
DOI: 10.1177/089124249801200105
|View full text |Cite
|
Sign up to set email alerts
|

Rural Networks in the United States: Lessons from Three Experiments

Abstract: A number of states and countries have begun to encourage formation of flexible manufacturing networks among small manufacturing and other firms to respond effectively to local economic crises or to enable smaller firms to compete more effectively in the global economy. A variety of strategic approaches have been employed, including funding organizations with a mandate to organize and support networks, and offering challenge grants to groups of firms to interest them in experimenting with a new organizational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…In other words, what aspects of the social structure of a rural community increase the likelihood entrepreneurs will be willing to cooperate? Several authors have emphasized the importance of social capital in a rural community for business networking and economic development Sommers, 1998;Woodhouse, 2006). However, it was Flora and Flora (1993) who first explained how different configurations of social capital might facilitate or impede collective action.…”
Section: Business Network Formation In Rural Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, what aspects of the social structure of a rural community increase the likelihood entrepreneurs will be willing to cooperate? Several authors have emphasized the importance of social capital in a rural community for business networking and economic development Sommers, 1998;Woodhouse, 2006). However, it was Flora and Flora (1993) who first explained how different configurations of social capital might facilitate or impede collective action.…”
Section: Business Network Formation In Rural Communitiesmentioning
confidence: 99%
“…Beginning in the mid-1980s, interfirm collaboration as a means of rural development became a widely explored option in Europe (Rosenfeld, 2001;Sommers, 1998). The northern Italian region of Emilia Romagna provided the prototype for networks of small, independent firms formed to enhance competitiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing networks among rural manufacturers has long been considered an important approach to strengthening the competitiveness of rural SMMs (Sommers, 1998). Sommers (1998) found that three regional network experiments had a "modest" impact on business performance. The study concludes that, when developing networks, policy makers need to account for size and capacity of firms, stage of development of respective firms (funding for start-up vs. capital for more established firms), and soft versus hard networks.…”
Section: Context and Review Of Existing Literaturementioning
confidence: 99%
“…The study concludes that, when developing networks, policy makers need to account for size and capacity of firms, stage of development of respective firms (funding for start-up vs. capital for more established firms), and soft versus hard networks. Soft networks comprise capacity-building institutions, often economic development agencies, while hard networks include similar businesses attempting to develop new products or enter new markets (Sommers, 1998). The key to success in these types of networks is employer participation, as employers are less likely to participate in programs with government agencies (Green & Galetto, 2005).…”
Section: Context and Review Of Existing Literaturementioning
confidence: 99%